Equine infectious anemia virus worldwide prevalence : A 24-year retrospective review of a global equine health concern with far-reaching implications - Thieulent, Côme J. (2025)
Equine Infectious Anemia Virus (EIAV), the causative agent of Equine Infectious Anemia (EIA), presents a significant threat to equine populations worldwide. While local EIAV prevalence has been estimated in several studies, no global prevalence has been determined. Thus, this study aimed to review the literature on EIAV prevalence in the 21st century. A comprehensive electronic search was conducted in PubMed, Web of Science, Scopus, Google Scholar, SciELO.org, African Journals Online, and NZresearch.org, yielding 105 articles published between January 1st, 2000, and December 31st, 2024 (spanning 24 years). EIAV prevalence was estimated in 42 countries and is particularly high in Mexico (North America; 27.14 % [95 % CI, 25.11 – 29.17]) and Guatemala (Central America; 15.9 % [95 % CI, 9.66 – 22.14]). While EIAV prevalence in the United States of America (USA) remains low and stable over time, the relatively elevated prevalence in the Southern states, along with their extensive border with Mexico, places these areas at a higher risk. EIAV prevalence estimated per province/state in the USA, Argentina, and Brazil, indicated higher rates in humid and warmer regions. EIAV has a low presence in the Middle East, while the scarcity of epidemiological studies in Africa and Oceania complicates the estimation of EIAV prevalence in these regions. These findings highlight the need for continued intensive surveillance in both high-risk regions and areas lacking data. Given that insect vectors are the primary natural transmission route, global warming may lead to increased vector movement into temperate areas, potentially contributing to a surge in EIAV infections.